Systemic steroid treatment of rarely seen genitourinary system manifestation in children with Henoch Schönlein purpura: Case report and literature analysis (Annals of Medical Research, 2021)
None
Keywords: Balanitis; child; Henoch-Schönlein purpura; penile-scrotal involvement; treatment